The association between RANK, RANKL and OPG gene polymorphisms and the risk of rheumatoid arthritis: a case-controlled study and meta-analysis. Issue 6 (28th June 2019) - Yang, Haoyu; Liu, Weixi; Zhou, Xindie; Rui, Huan; Zhang, Hui; Liu, Ruiping
Abstract : The receptor activator of nuclear factor-κB (RANK) and the osteoprotegerin (OPG) cascade system have been reported to be essential in osteoclastogenesis. In recent years, several studies have investigated the association between polymorphisms of RANK, its ligand RANKL and OPG genes and the risk of rheumatoid arthritis (RA) in different populations. However, the results arising from these studies were conflicting. To determine the association between RANK, RANKL and OPG gene polymorphisms and the risk of RA. We conducted a hospital-based case-controlled study in Changzhou with 574 RA cases and 804 controls. The genotyping of RANK gene rs1805034 polymorphism was conducted by single base extension combined with matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF-MS). We also undertook a meta-analysis of the literature referring to polymorphisms of RANK, RANKL and OPG genes and RA risk. This case-controlled study found that the polymorphism in the RANK gene rs1805034 was not related to RA risk. Stratification analyses by sex and age suggested that RANK gene rs1805034 polymorphism was not associated with the risk of RA among groups of male, female, age ≤ 55 and age > 55. Our meta-analysis found that the rs2277438 polymorphism in RANKL gene increased the risk of RA, whereas RANK gene rs1805034, OPG gene rs3102735, OPG gene rs2073618, OPG gene rs3134069 polymorphisms were not related to RA susceptibility. In conclusion, this case-controlled study and meta-analysis indicated that the RANKL gene rs2277438 polymorphism increased the RA risk, and that RANK gene rs1805034, OPG gene rs3102735, OPG gene rs2073618, OPG gene rs3134069 polymorphisms were not related to RA risk.